2016
DOI: 10.1111/jocn.13194
|View full text |Cite
|
Sign up to set email alerts
|

Somatic symptoms, sleep disturbance and psychological distress among women undergoing oocyte pick‐up and in vitro fertilisation–embryo transfer

Abstract: Assisted reproductive technologies nurses can assess women's psychological distress by caring for their sleep disturbance without directly exploring their mood state. Moreover, these medical personnel should understand infertile female patients' psychological distress is mainly associated with their sleep disturbance. Developing various strategies to improve both sleep quality and psychological distress for infertile female patients should be recognised in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
2
21
0
2
Order By: Relevance
“…Factors exacerbated by sleep deprivation [19,38,80,130], including excessive sympathetic activation [1,4,104], oxidative stress [31,49], and increased ghrelin [66] may be detrimental to IVF outcomes. Additionally, psychological distress, which could be mediated by poor sleep [70], may reduce IVF success [56] or result in discontinuation of the IVF process [43]. Therefore, sleep remains an under-investigated, modifiable target that may provide a non-pharmacological, cost-effective, and patient-centered avenue to improve IVF outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors exacerbated by sleep deprivation [19,38,80,130], including excessive sympathetic activation [1,4,104], oxidative stress [31,49], and increased ghrelin [66] may be detrimental to IVF outcomes. Additionally, psychological distress, which could be mediated by poor sleep [70], may reduce IVF success [56] or result in discontinuation of the IVF process [43]. Therefore, sleep remains an under-investigated, modifiable target that may provide a non-pharmacological, cost-effective, and patient-centered avenue to improve IVF outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbances are thought to be common in women undergoing infertility treatment [36] despite minimal data to support this hypothesis [69,70,84]. In one investigation evaluating a heterogeneous group of women in infertility clinic, 34 % answered yes to the question Bdo you experience disturbed sleep^ [84].…”
Section: Sleep Disturbances In Women Undergoing Infertility Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The same study team assessed the PSQI in women undergoing IVF and found that 23% of women had poor sleep during oocyte retrieval and 46% had poor sleep at the time of embryo transfer. 7 …”
Section: Introductionmentioning
confidence: 99%
“…17 Not surprisingly, women with disturbed sleep (as measured by the PSQI) were 2-3 times more likely to display psychological distress during the IVF process. 7 Despite the vulnerability of this group to stress and resultant sleep disruption, the impact of poor quality sleep on reproductive outcomes during IVF, in conjunction with or independently from psychological stress, remains unknown.…”
Section: Introductionmentioning
confidence: 99%